Models of Opposing Against Job Stress among Military Staff - Esfandear Azadmarzabadi; Saeed Niknafs (Tehran University of Medical Sciences, 2016)
Background and Aim: People use various ways against the stresses. Choosing a suitable confront ways can reduce the influence of stresses on individuals is mental health and lead to more compatibility. Therefore, the purpose of the current survey was to investigate the methods of opposing against job stress in military staff. Materials and Methods: The procedure was of descriptive-analytical type, and it was implemented through questionnaires. Two types of questionnaires, job stress and coping with stressor situation, were handed in to number of 959 individuals as the sample of the research. Percentiles, frequencies, averages and standard deviations were obtained through descriptive statistics. Statistical method of T between the two samples and multi-variable regression model were used to analyze the data. All analyses were performed in SPSS package version 18.  Results: Results showed that job stress within sample group had the best condition concerning sub-component of "role" with average of 3.79 and standard deviation of 0.86, whereas the worst condition was related to sub-component of "communication" with average of 2.77 and standard deviation of 0.84. Military staff use problem-base mode to cope with their stressors. Regression coefficients also suggested that only exciting-base mode can predict job stress.   Conclusion: Problem-base mode is the most used method by military in coping with stressful situations.